How is the Quality of E-Learning Developed by Mathematics Perspective Teachers? - Palupi, Evangelista Lus Windyana; Fardah, Dini Kinati (SHS Web of Conferences, 2022)
This study aims to examine the quality of 8 e-learning design developed by perspective mathematics teachers. The instrument used was an observation sheet consisting of 25 dimensions observed related to 6 fields, namely tutor support, collaboration, technology, information transparency of provider/course, course structure, and didactics. The results of this study indicate that of the 8 e-learning designs developed, most of the designs have met all the aspects in each field. However, the design left out the Individualized Learner Support since the designed e-learning is only focused on the particular topic on mathematics and the support needed beyond the topic is provided by teacher through other form such as class WhatsApp group in where students and teachers interaction are not limited only on the particular topic.Another aspect left out is Traditional Communication Media since it already covered by more sophisticated media like video conference, google drive and WhatsApp. Organisational Information is not yet paid attention in the designing the e-learning which could be added for better information on the course detail.Regarding the discursive cooperation and discussion, all the 8 designed e-learning provide the problem to be discussed but only 6 out of 8 of the designed e-learning promote classroom discussion with discursive problem.